1993
DOI: 10.1002/pssa.2211370114
|View full text |Cite
|
Sign up to set email alerts
|

Effects of YBa2Cu3Oy Doping into Bi2Sr2Ca2Cu3Ox on Superconducting Properties

Abstract: The effects of YBa2Cu3Oy (YBCO) doping into Bi2Sr2Ca2Cu3Ox (BSCCO) on superconducting properties are investigated. With increasing doping concentrations of YBCO from 2 to 20 wt%, Tc of the samples decreases from 100 to 80 K. However, scanning electron microscope and X‐ray diffraction results indicate that both BSCCO (Tc > 100 K) and YBCO (Tc > 90 K) exist in the samples. The decrease of Tc of the samples may be due to the deviation of the oxygen content of the BSCCO from the optimum one for high Tc, which is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
1995
1995

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…The J , values of the Bi-based superconducting ceramics were still low because of flux creep, weak coupling, etc. [4, 51. Of late, it was reported that samples prepared by the melt-powder-melt growth process [6,71 and by doping impurities [8] to the sample as pinning centers showed high J,. The J , values of the superconducting ceramics seem to be very sensitive to the preparation conditions of ceramics.…”
Section: Introductionmentioning
confidence: 99%
“…The J , values of the Bi-based superconducting ceramics were still low because of flux creep, weak coupling, etc. [4, 51. Of late, it was reported that samples prepared by the melt-powder-melt growth process [6,71 and by doping impurities [8] to the sample as pinning centers showed high J,. The J , values of the superconducting ceramics seem to be very sensitive to the preparation conditions of ceramics.…”
Section: Introductionmentioning
confidence: 99%